2008
DOI: 10.1002/adma.200800366
|View full text |Cite
|
Sign up to set email alerts
|

Organic Photovoltaic Devices Based on a Novel Acceptor Material: Graphene

Abstract: Solution‐processable functionalized graphene (SPFGraphene, see figure) is used as the electron‐accepting material in organic photovoltaic (OPV) devices for the first time, showing that it is a competitive alternative. The fabrication and performance of bulk heterojunction OPV devices with SPFGraphene and different donor materials is presented, together with the impact of post‐fabrication annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
489
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 824 publications
(505 citation statements)
references
References 51 publications
9
489
1
6
Order By: Relevance
“…However, it cannot be directly used as a filler of hydrophobic organic polymers such as polythiophene derivatives because it is hydrophilic. 109 Consequently, functionalization of GO is important for improving its dispersibility in organic matrices. For example, phenyl isocyanate (PIC) was used to synthesize organic solution-processable functionalized graphene.…”
Section: Heterojunction Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it cannot be directly used as a filler of hydrophobic organic polymers such as polythiophene derivatives because it is hydrophilic. 109 Consequently, functionalization of GO is important for improving its dispersibility in organic matrices. For example, phenyl isocyanate (PIC) was used to synthesize organic solution-processable functionalized graphene.…”
Section: Heterojunction Solar Cellsmentioning
confidence: 99%
“…As a novel and unique member of the carbon nanomaterials family, graphene is an attractive material for fabricating transparent electrodes 27,43,141 and improving the performances of dyesensitized 15,142,143 and heterojunction solar cells. [108][109][110] Transparent Conducting Electrodes TCEs are a key component of optoelectronic devices. The ideal TECs should possess high transparency (>80%), low resistance (<100 X/&), and an appropriate work function (4.5-5.2 eV).…”
Section: Solar Cellsmentioning
confidence: 99%
“…The latest results 16,21,24 including our own studies 31 have demonstrated that the efficacious use of graphene in polymer nanocomposites is strongly correlated with the ability to disperse them homogeneously in a polymer matrix without destroying their integrity of graphitic network. Perfect graphene does not exist naturally, but bulk and aqueous or organic solution processable functionalized graphene materials can now be prepared easily.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Great strides have been made in the use of solution-processable graphene materials for highly conducting composites, [18][19][20] transparent electrodes 21 and photovoltaic device applications. 22,23 Currently, graphene, which is a perfect monolayer that does not exist naturally, can be produced in large quantities by the chemical reduction of graphene oxide (GO), using graphite as a raw material. 24 Graphite is cheap and easily available, so this chemical approach is likely to be the simplest and most effective method for the large-scale production of graphene.…”
Section: Introductionmentioning
confidence: 99%